A dynamic analysis scheme for the suspended monorail vehicle–curved bridge coupling system. Issue 8 (June 2020) - Bao, Yulong; Xiang, Huoyue; Li, Yongle
Based on the rigid–flexible coupling method, an original scheme for the dynamic analysis of the vehicle–bridge interaction between suspended monorail trains and horizontally curved bridges is proposed. Considering the compression deformation and contact model of walking tire and guiding tire, the geometric and mechanical coupling relationships between vehicle and bridge are studied, and the dynamic equations of suspended monorail vehicle–bridge interaction are derived. A vehicle–curved bridge coupling vibration system is established according to transformable relationship between the local coordinate system and the global coordinate system in SIMPACK. Considering a curved bridge under passage of suspended monorail vehicles as an example, the influences of critical system parameters, such as the superelevation, vehicle speed, and bridge curve radius, on the dynamic responses of vehicles and the curved bridge are explored. It is shown that the direction of the yawing moment of the front bogie is in accordance with the turning direction of the vehicle, while the yawing moment of the rear bogie is in the opposite direction. The superelevation has great influence on the lateral guiding force and vertical walking force of vehicle, and vehicle speed is a key factor to the running safety of suspended monorail vehicle. In addition, the curve negotiation ability of vehicle is better with the increase in bridge curve radius.